PENGARUH MEDIA SOSIAL TERHADAP BISNIS ONLINE - Erista, Monica; Pandriadi, Pandriadi; Dini, Maya (Jurnal Akuntansi, Auditing dan Investasi, 2025)
This research aims to determine the influence of social media on growth, marketing and customer interactions in online businesses. By using social media points, businesses can increase brand awareness and encourage wider customer conversations. Interactive functions such as Instagram, Facebook, and TikTok can also be used wisely to deliver product messages in a visual and inspiring manner and increase customer support who like to support business products. Social media has also faced important challenges since then, where content management is relevant and flexible and attention is paid to heritage by the public. Even though the potential for online business based on social media is enormous, it is actually important to develop the right strategy to maximize its benefits in increasing the business effectively. Kata kunci: social media, online business, digital marketing, interaction between customers, marketing strategy.